2023
DOI: 10.1136/gutjnl-2022-328258
|View full text |Cite
|
Sign up to set email alerts
|

Patient selection for urgent endoscopic retrograde cholangio-pancreatography by endoscopic ultrasound in predicted severe acute biliary pancreatitis (APEC-2): a multicentre prospective study

Abstract: ObjectiveRoutine urgent endoscopic retrograde cholangiopancreatography (ERCP) with endoscopic biliary sphincterotomy (ES) does not improve outcome in patients with predicted severe acute biliary pancreatitis. Improved patient selection for ERCP by means of endoscopic ultrasonography (EUS) for stone/sludge detection may challenge these findings.DesignA multicentre, prospective cohort study included patients with predicted severe acute biliary pancreatitis without cholangitis. Patients underwent urgent EUS, foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…To the contrary, ERCP may be associated with significant procedurerelated complications [42]. Here it should also be acknowledged that our approach with early EUS might not have always been justified since the EUS-guided ERCP approach, even in predicted severe pancreatitis, did not reduce major complications or mortality compared to the conservative strategy in APEC trials [37,38]. This might be even more relevant in predicted mild pancreatitis.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…To the contrary, ERCP may be associated with significant procedurerelated complications [42]. Here it should also be acknowledged that our approach with early EUS might not have always been justified since the EUS-guided ERCP approach, even in predicted severe pancreatitis, did not reduce major complications or mortality compared to the conservative strategy in APEC trials [37,38]. This might be even more relevant in predicted mild pancreatitis.…”
Section: Discussionmentioning
confidence: 93%
“…The APEC trials failed to demonstrate a difference for the primary outcome, which was a composite of mortality or major complication occurring within 6 months of randomization. The only component of the primary outcome with a difference between groups was cholangitis, which was less common in the urgent ERCP group than in the conservative treatment group (2% versus 10%) [37,38]. The findings of the APEC studies, in conjunction with prior work, emphasize that expecting ERCP to stop or reverse the pathophysiological mechanisms resulting in systemic and local complications in acute pancreatitis is overly optimistic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a systemic review of eight RCTs, early ERCP in patients without cholangitis did not reduce the risk of overall pancreatic complications, organ failure or death [59]. Especially among patients with predicted severe acute biliary pancreatitis but without cholangitis, the results of recent APEC and APEC-2 trials showed that urgent ERCP, even when guided by EUS to select patients with biliary stones and sludges in the APEC-2 trial, failed to significantly reduce major complications or mortality compared to conservative treatment [69,70]. As a result, there has been a growing inclination towards a more conservative strategy, reserving ERCP for cases where there is a clear indication, such as the presence of cholangitis or persistent biliary obstruction.…”
Section: Timing and Role Of Ercp And Endoscopic Ultrasonography (Eus)...mentioning
confidence: 99%
“…in a historical control group [67]. If ES has been performed because of biliary pancreatitis, it very likely prevents recurrent biliary pancreatitis or at least significantly reduces the risk of pancreatitis, hence cholecystectomy after ES serves to prevent other complications caused by the gallbladder stones (e.g., acute cholecystitis).…”
Section: Accepted Manuscriptmentioning
confidence: 99%